Board Diversity and Risk Management: Impact on Disclosure Quality and Cost of Capital in the Financial Sector - Ardila, Sidiq (Cattleya Darmaya Fortuna, 2024)
This study examines the role of board diversity in risk managementand its impact on the quality of risk disclosure and the cost of capitalin financial institutions. Using a panel-based quantitative-empiricaldesign (2019–2025), this study develops two key constructs: a multidimensionalBoard Diversity Index (BDI) (demographic: gender,age, nationality; and functional: risk/audit/compliance expertise,IT/data security, risk committee, frequency of risk meetings) and aRisk Disclosure Quality Index (RISQ) that assesses substantivecontent (exposure specificity, limits and risk appetite, quantitativemetrics such as PD/LGD/VaR, scenarios/stress, and linkages tocapital and strategy). The impact on the cost of equity capital (COE)and the cost of debt (COD) is estimated using panel regression (firm& year fixed effects), mediation tests (bootstrap/SEM), and robusttests (alternative proxies, winsorizing, index redefinition). Theresults show that IKD has a positive effect on IKPR, mainly throughthe dimensions of functional expertise and strengthening boardprocesses (committees & risk agenda). Furthermore, IKPR isnegatively associated with COE and COD, indicating a decrease ininformation asymmetry and risk premium. The direct effect of IKDon the cost of capital is smaller than the mediation channel throughIKPR, confirming the mechanism: board diversity → increaseddisclosure quality → decreased cost of capital. Heterogeneityanalysis shows a stronger effect in high-risk environments,emphasizing the role of materiality. The research's primarycontribution is a risk-capability-oriented measure of board diversityand an assessment of the quality of auditable disclosures, beyondquantitative measures. Practical implications recommendstrengthening board composition (risk/audit/compliance, ITexpertise), institutionalizing risk committees and agendas, andfocusing on specific, measurable disclosures linked to capital andstrategy.